Tafsir Nusantara dan Isu-isu Global: Studi Kasus Relevansi Pemikiran Hamka tentang Keadilan Sosial, Kesetaraan Gender dan Pluralisme - Thoriqul Aziz; Ahmad Zainal Abidin; Muthmainnatun Nafiah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2020)
This article discusses the relevance of Hamka's thought in Tafsir al-Azhar pertaining to global issues in modern life. Hamka is an Indonesian Muslim scholar who is well recognized. He is a modernist interpreter who writes his tafsir in Indonesian. With a descriptive-analytical method, this study reveals the contribution of Hamka's thinking in the three most challenging global domains in Muslim scholarship on issues of social justice, gender equality and religious plurality. From his thoughts it can be concluded: First, in the realm of social justice; according to Hamka, all humans have the same rights and degrees in the social and legal perspective. Second, in the realm of gender equality; men and women have equal right and there is no difference in the realm of humanity. Third, in the realm of religious plurality, Hamka believes that there is plurality in diversity. Therefore, tolerance is a necessity for every human being. The three themes carried by Hamka are based on the teachings of Islam that are very concerned about human values. Hamka's interpretation above confirms the teachings of Islam which are apropriate for all times.